Prevalence of different states of glucose intolerance in Sri Lankan children and adolescents with obesity and its relation to other comorbidities. Issue 2 (4th November 2020) - Ciba, Iris; Warnakulasuriya, Loretta S.; Adikaram, Adikaram V. N.; Bergsten, Peter; Dahlbom, Marie; Fernando, Manel M. A.; Rytter, Elisabet; Samaranayake, Dulani L.; Silva, K. D. Renuka Ruchira; Wickramasinghe, V. Pujitha; Forslund, Anders H.
Abstract: Background: South Asian adults have higher prevalence of obesity comorbidities than other ethnic groups. Whether this also is true for Sri Lankan children with obesity has rarely been investigated. Objective: To investigate prevalence of glucose intolerance and other comorbidities in Sri Lankan children with obesity and compare them with Swedish children. To identify risk factors associated with glucose intolerance. Subjects: A total of 357 Sri Lankan children (185 boys), aged 7 to 17 years with BMI‐SDS ≥2.0 from a cross‐sectional school screening in Negombo. A total of 167 subjects from this study population were matched for sex, BMI‐SDS and age with 167 Swedish subjects from the ULSCO cohort for comparison. Methods: After a 12 hour overnight fast, blood samples were collected and oral glucose tolerance test was performed. Body fat mass was assessed by bioelectrical impedance assay. Data regarding medical history and socioeconomic status were obtained from questionnaires. Results: Based on levels of fasting glucose (FG) and 2 hours‐glucose (2 hours‐G), Sri Lankan subjects were divided into five groups: normal glucose tolerance (77.5%, n = 276), isolated impaired fasting glucose according to ADA criteria (9.0%, n = 32), isolated impaired glucose tolerance (8.4%, n = 30), combined impaired fasting glucose (IFG) + impaired glucose tolerance (IGT) (3.1%, n = 11) and type 2 diabetes mellitus (2.0%, n = 7). FG, 2 hours‐insulin and educational status of the father independently increased the Odds ratio to have elevated 2 hours‐G. Sri Lankan subjects had higher percentage of body fat, but less abdominal fat than Swedish subjects. Conclusion: High prevalence in Sri Lankan children with obesity shows that screening for glucose intolerance is important even if asymptomatic.